Sustainable tourism in mountain protected areas of asturias: An analysis from tourists' perceptions and profiles - Magadán Díaz, Marta; Rivas García, Jesús Israel (Sustainable Development of Mountain Territories, 2020)
Tourism can act as an important engine for rural development in peripheral mountain communities that often face many economic, social and environmental challenges [1]. In fact, although tourism activity has become a primary source of income for many mountain areas [2], the environmental impact of tourism can be particularly critical and significant in these ones [3], mainly due to a: i) lack of infrastructure, and ii) lack of sustainable planning policies by the authorities [4]. Mountain tourism includes multiple forms: skiing, mountaineering, hiking or climbing; In addition, other active tourism modalities such as cycle tourism or canyoning have been incorporated [2; 5]. Tourism activities in mountain areas can be beneficial to settle the population, in addition to improve people's quality of life in the mentioned areas, through sustainable development and environmental preservation [4; 6]. In addition, mountain tourism can contribute both to maintain biodiversity [7] and promoting sustainable rural development in mountain areas [8, 9]. Nevertheless, the areas where such activities take place are often considered environmentally vulnerable [10; 11] and therefore it is vitally important to establish long term sustainable tourism activities. In short, the coexistence of tourism and the primary activities of mountain regions should be aimed at maximizing the sustainability of the area [1; 12], so that agricultural and environmental policies-both at European, national and local levels-ensure a harmonious coexistence of primary activities with tourism [13]. This research aims to analyse the tourists perception in a mountain environment (Asturias, in the Northwest of Spain), studying their opinions on environmental sustainability in two main aspects, namely, i) the importance of experiencing virgin nature and ii) the choice of holiday accommodation without carbon emissions, for which the following research questions (RQ) are posed: (RQ1) What is the perception of sustainability among mountain tourists in Asturias? (RQ2) What sociodemographic factors can influence the propensity to increase expenses related to a sustainable holiday offer? The aforementioned questions are answered through a survey study conducted among tourists staying in the main mountain areas of Asturias and, finally, some recommendations are proposed for both policy-makers and practitioners. The paper is structured as follows. Section 2 offers a brief description of Asturias, the Spanish region that has been chosen for the case study. Section 3 collects both the literature review and the research approach. Section 4 presents the research methodology, sample design, data analysis, as well as the discussion of findings. Finally, Section 6 sets the conclusions derived from the research conducted.
Keywords: Asturias; best-worst scale; biosphere reserve; regression analysis; sociodemographic factors; survey method; sustainable tourism; tourists perception; Scopus